Atmospheric turbulence characterization using a neuromorphic camera-based imaging sensor. (26th November 2021) - Polnau, Ernst; Vorontsov, Mikhail A
Abstract: New capabilities for atmospheric turbulence spatio-temporal dynamics characterization and refractive index structure parameter ( C n 2 ) sensing via white light imaging of remotely located non-cooperative targets using an optical system with a neuromorphic (event) based sensor are demonstrated through a set of experimental trials conducted over a 7 km imaging path and proposed event data processing technique.